Removal of a Horizontally Displaced Dental Implant below the Mandibular Canal - Khodor Ahmed Fakih; Maria Stiliyanova Edreva; Biser Borisov Stoichkov (Case Reports in Dentistry)
A clinical case of a horizontally displaced dental implant, which moved below the level of the mandibular canal during surgery is presented together with a brief review of the comparable published cases. The bone mineral density and the morphology of the alveolar ridge were analyzed at the site of osteotomy, and the low bone density of 265.32±86.41 Hounsfield Units was found in the area. The factors related to implant displacement were: the anatomical features of bone structure, and the applied mechanical pressure during the implant insertion. The displacement of the dental implant below the level of the mandibular canal during implantation can be a severe complication. Its removal requires the safest surgical approach to avoid damaging the inferior alveolar nerve. The description of one clinical case does not provide grounds for drawing definite conclusions. To avoid similar incidents, detailed radiographic assessment before implantation is necessary; it is also important to follow the surgical protocols of implant placement into soft bone and to create conditions for a good visibility and sufficient control of bleeding during surgery.